A desinvenção da deficiência mental: um estudo da linguagem durante o uso de um jogo digital - Haag, Cassiano Ricardo (Universidade do Vale do Rio dos Sinos, 2011)
Mental retardation is, like any other concept in science, a social historical and discursive work. This concept, thus, has been changing, and researchers have sought answers to how to deal with this condition so that the people involved can have better quality of life. As much as the concept changes, however, it has never ceased to be based on the idea of intellectual limitations, and in this research, we believe that this is a crucial aspect of the problem. The research is empirical and investigates the language manifestations of an individual with this diagnosis during a play activity, discussing the hypothesis of limitation, restriction or disability to explain the development. The corpus is constituted of video recordings made at a public school in a city of Vale do Paranhana-RS. For the analysis of results, we dialogue with the view of development and learning proposed by Vygotsky (1989, 2001) related to the concepts of self-organization and chaos (Johnson, 2003). From the epistemological framework of Sociodiscursive interactionism (BRONCKART, 1999, 2006b) in the of language area, we explore a notion of meaning construction, comprised of four inseparable and complementary activities, namely, reference, co-construction of memory, production of hypotheses and anticipation of situations. These four activities are studied from the linguistic point of view and they seem to be sufficient to discuss the idea of intelligence limitation. The results allowed the verification of a cognitive instability which is manifested not only in language activity but also produced collectively by it.
Keywords: Deficiência mental; Desenvolvimento humano; Atividade de linguagem; Mental retardation; Human development; Language activity; ACCNPQ::Lingüística, Letras e Artes::Lingüística